Taxonomia integrativa de Thaptomys Thomas, 1916 (Rodentia: Cricetidae) - Colombi, Victor Hugo (2018)
Thaptomys Thomas, 1916 is a monotypic rodent genus endemic from Atlantic Forest. Despite the low morphological differentiation, cytogenetic and molecular data suggest an underestimated diversity for this taxon. Thus, the present work tested the hypothesis that Thaptomys is not monotypic, from an integrative analysis, with cytogenetic, morphometric (secondary data), molecular and niche modeling data, performing a broad taxonomic revision for the genus. We analyzed 201 specimens (141 citogenectilly) of 26 localities, from Una/BA to San Raphael, Paraguay. G and C banding, FISH with telomeric probes and chromosome painting allowed the characterization of five new karyotypes, described for the first time: 2n=48/FNA=52, 2n=49a/FNA=52, 2n=49b/FNA=52, 2n=50/FNA=52, 2n=51/FNA=52. Our data suggest that centric fusions of four acrocentrics pairs (1+15 and 3+4) generated a large metacentric and other submetacentric pairs, in homozygous and heterozygous conditions, combinations at 2n=48-51/FNA=52. In addition, we refined the mechanism of differentiation between karyotypes of 2n=50/FNA=48 and 2n=52/FNA=52, as a complex rearrangement involving unequal centric fission of each small metacentric 25 homologue, followed by a tandem fusion of each arm derived from 25 in the acrocentric pairs 2 and 23. Phylogenetic analyzes (Cytb) recovered a "Noth Clade" of wide geographic range, from Una/BA (2n=50/FNA=48), Luminárias/MG (2n=48-51/FNA=52) to Tapiraí/SP (2n=52/FNA=52) and the other samples formed a politomy ("South"), from Tapiraí/SP (2n=52/FNA=52) to San Rafael and Limoy (Paraguay, without karyotype), which diverged by 2.15%. Specimens with different karyotypes were not recovered as monophyletic, although specimens with 2n=50/FNA=48 formed two distinct and exclusive clades. Population analysis (CytB and six microsatellite loci) indicated Una/BA (2n=50/FNA=48) as a distinct population from the others, diverging in 1.89% from 2n=52/FNA=52 and 1.2% of 2n=48- 51/FNA=52, without sharing of haplotypes with another karyotype or locality. Morphologically, specimens with 2n=48-51/FNA=52 did not present any distinction of those with 2n=50/FNA= 48 and 2n=52/FNA=52 and that are geographically isolated. The geographic distribution of the different karyotypes shows that they were never detected in sympatry, that there is no evidence of hybrids between them and that they seem to be geographically isolated, since Una/BA (2n=50/FNA=48) is distant in 938 km of Luminárias/MG (2n=48-51/FNA=52), and 500km from Santa Teresa/ES (2n=52/FNA=52). The fixation of a chromosomal rearrangement with a high frequency in a population, such as the central fissions and tandem fusions observed in specimens with 2n=50/FNA=48, would result in separation of Thaptomys populations into non interbreeding subgroups (with and without chromosomal rearrangement), representing a barrier to gene flow, as suggested in the peripatric speciation model. Thus, founding populations of small size would tend to represent distinct species, the chromosome being the triggering factor of this process. The lack of phylogenetic resolution in recovering specimens with different karyotypes as monophyletic, added to the subtle (not significant) morphological distinction, may indicate a process of abrupt speciation, started by complex chromosomal rearrangements in which the lineages did not have time to accumulate differences. In view of the data, a much more complex interpretation is proposed, in which Thaptomys would be represented by two species, being (I) Thaptomys sp. n., with 2n=50/FNA=48, exclusive from Una, Bahia; and (II) Thaptomys nigrita, presenting chromosomal polymorphism, with three subspecies, being (III) Thaptomys nigrita ssp. n with 2n=48-52/FNA=52, exclusive from Luminárias, Minas Gerais, (IV) Thaptomys nigrita nigrita (nominotypical subspecies; 2n=52/FNA=52), occurring from Santa Teresa (ES) to Tapiraí (SP) and (V) Thaptomys nigrita subterraneus (2n=52/FNA=52), from Pilar do Sul (SP) to San Raphael (Paraguay).